The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2147/opth.s61444
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of travoprost solution for the treatment of elevated intraocular pressure

Abstract: Travoprost is a prostaglandin analogue widely used for reducing intraocular pressure (IOP) in patients affected with glaucoma and ocular hypertension. It exerts its ocular hypotensive effect through the prostaglandin FP receptors, located in the ciliary muscle and the trabecular meshwork. Several studies have shown that topical administration of travoprost induces a mean IOP reduction ranging from 25% to 32%, and sustained throughout the 24-hour cycle. When compared with timolol, travoprost is more effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 94 publications
(115 reference statements)
0
12
0
3
Order By: Relevance
“…TTFC has been reported to have a neutral pH, which allows for the high permeability of the β component into the eye 17. Quaranta et al discussed the IOP-lowering effect of TTFC when switched from travoprost monotherapy in their review report 18,19. From their reports there is a possibility of greater IOP-lowering effect of TTFC when switched from travoprost than other FC when switched from each PGA.…”
Section: Discussionmentioning
confidence: 99%
“…TTFC has been reported to have a neutral pH, which allows for the high permeability of the β component into the eye 17. Quaranta et al discussed the IOP-lowering effect of TTFC when switched from travoprost monotherapy in their review report 18,19. From their reports there is a possibility of greater IOP-lowering effect of TTFC when switched from travoprost than other FC when switched from each PGA.…”
Section: Discussionmentioning
confidence: 99%
“…PGAs have demonstrated better IOP-lowering ability than β -blockers with fewer systemic adverse effects [8688]. They act by increasing uveoscleral and TM outflow and reduction in IOP starts 2–4 hours after first administration.…”
Section: Contemporary Pharmacological Management Of Glaucomamentioning
confidence: 99%
“…Several studies have shown that topical administration of travoprost leads to a mean IOP reduction from 25% to 32%, which is sustained throughout the 24-hour cycle [88, 89]. In a prospective, open-label, single-arm study conducted in Italy ( N = 36 previously untreated POAG patients), travoprost monotherapy at a dose of 0.004% administered once in the evening (8:00 pm) induced uniform 24-hour IOP reduction.…”
Section: Contemporary Pharmacological Management Of Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Using the impression citology, Sezgin Akcay et al 2014 found that polyquaternium (PP)-preserved travoprost is safer and better tolerated than benzalkonium chloride (BAK)-preserved travoprost. That's the reason why the compliance of patients increases (Quaranta 2015, Peace 2015. It may be an advantageous prostaglandin analog option for patients affected by open-angle glaucoma (OAG) or ocular hypertension (OHT) who are intolerant to BAK-preserved latanoprost or bimatoprost (Konstas et al 2017).…”
Section: Introduction:-mentioning
confidence: 99%